Cardiac damage induced by immunization with heat‐killed Trypanosoma cruzi is not antibody mediated. (13th December 2012) - Bonney, K. M.; Gifford, K. M.; Taylor, J. M.; Chen, C.‐I.; Engman, D. M.
Summary Cardiac inflammation that develops during infection with Trypanosoma cruzi may result in part from autoimmunity, which may occur after bystander activation, after parasite‐induced cardiomyocyte damage, or molecular mimicry. A/J mice infected with T. cruzi or immunized with heat‐killed T. cruzi (HKTC) develop strong autoimmunity accompanied by cardiac damage. To determine whether this cardiac damage occurs via an antibody‐dependent mechanism, we analysed T. cruzi‐infected and HKTC‐immunized mice for the presence of autoantibodies, cardiac antibody deposition, and serum cardiac troponin I as a measure of cardiac damage. We also performed a serum transfer experiment in which sera from T. cruzi‐infected and T. cruzi‐immunized mice (and controls) were transferred into naïve recipients, which were then analysed for the presence of antibodies and serum troponin. Unlike T. cruzi‐infected mice, T. cruzi‐immunized mice did not show significant antibody deposition in the myocardium. These results indicate that antibody deposition does not precede cardiac damage and inflammation in mice immunized with or infected with T. cruzi. Serum adoptive transfer did not induce cardiac damage in any recipients. Based on these findings, we conclude that the cardiac damage induced by immunization with HKTC is not mediated by antibodies.